MODEL PANEL DATA DALAM MENGANALISIS DETERMINAN PADA RETURN SAHAM DI INDONESIA: STUDI KASUS JAKARTA ISLAMIC INDEX - Yudhistira Ardana (Reinforce: Journal of Sharia Management, 2022)
As a potential investor, you should analyze the financial performance of a company. Several methods that can be used are Economic Value Added, Market Value Added, and Cash Value Added. This study aims to analyze the factors that affect stock returns in companies listed on the Jakarta Islamic Index using the panel data model. The independent variables used in this study are EVA, MVA, and CVA. While the dependent variable is stock returns. The results showed that all the variables used in this study, namely EVA, MVA, and CVA, influenced stock returns in companies listed in JII. This is evidenced by the probability value of less than 5% (0.014374 < 0.05). These variables have a percentage in influencing stock returns of 32.91%, while the remaining 67.09% is influenced by other variables outside the model used. Meanwhile, independently, it can be concluded that EVA and CVA have no significant effect and have a negative correlation with stock returns. Meanwhile, MVA has a significant and positive correlation.